Nanotechnology-assisted cryopreservation of ovine semen: evaluation of Thymus vulgaris essential oil as a natural antioxidant - Khnissi, Samia; Maaloul, Rania; Chalouati, Hela; Mara, Laura; Aouadi, Dorra; Adouani, Basma; Dattena, Maria; Khémiri, Ikram; Fattouch, Sami (Frontiers in Animal Science, 2025)
The objective of the present study was to evaluate the protective effects of nanoemulsion of thyme (Thymus vulgaris) essential oil (EO) during the liquid state preservation of ram semen. Storage media were prepared: one containing Thymus vulgaris essential oil (Th), another with its nanoemulsion form (NTh), and a control sample without essential oil (Dovx). The quality of the semen diluted in the prepared media after preservation at 4°C and 15°C was examined by measuring the two parameters indicative of semen quality: semen motility and progressivity refer to the ability of ram sperm cells to move actively and efficiently, which is crucial for successful fertilization. The results showed a decrease in the mobility and progressivity of the sperm in all the mediums, but the thyme EO and its nanoemulsion showed slight decreases compared to the control medium (p<0.05). On the other hand, the study identified a negative impact of thyme EO nanoemulsions on catalase concentrations, potentially leading to mobility inhibition (p<0.05). In addition, the nanoemulsion significantly (p<0,05) decreased the malondialdehyde concentration, increased the total protein and the glucose contents, the lactate dehydrogenase activity. A significant decrease in calcium content was observed (p < 0.05). The essential oil of Thymus vulgaris, combined with nanotechnology encapsulation as a delivery method (nanoemulsion), demonstrated a notable and effective role in enhancing the preservation of ovine semen.